Optimizing the Rheological and Textural Properties of Chapatti Enriched with House Crickets (Acheta domesticus) Flour Using Hydrocolloids by an I-Optimal Design - Habiba Khatun; Siebe Lievens; Ruben Smets; Mohammad Akhtaruzzaman; Mik Van Der Borght; Johan Claes (Foods, 2022)
The fortification of food with edible insect flour can improve its nutrition profile, but also affect its techno-functional characteristics. In this study, an I-optimal design was applied to improve the rheological and textural properties of wheat flour chapatti containing 10% cricket (Acheta domesticus) flour. More specifically, the impact and optimal addition of hydrocolloids (carboxymethyl cellulose, hydroxypropyl methylcellulose, guar gum and xanthan gum) and water content were studied. For all the responses, the model and model terms were highly significant and showed the different impact of the hydrocolloids on the rheological properties. To evaluate the predictive power of the models, two sets of optimal process settings were chosen: one based on dough properties, and another on baked chapatti. For both sets, the actual responses were in the range of predicted responses for almost all properties. In addition, it was shown that using the settings based on dough properties, the actual responses were not significantly different from the control chapatti, whereas for the settings based on baked chapatti, there were differences in terms of the extensibility of both dough and chapatti. Thus, the I-optimal design is suitable to optimize the dough properties and the baked chapatti when enriching chapatti with cricket flour.